Botanical Roots and Word Origins: A Systematic Reconstruction of Alor Plant Name Etymologies - Brenda Man Qing Ong; Francesco Perono Cacciafoco (Histories)
This research provides a systematic reconstruction of nine botanical names from the Papuan languages spoken on Alor Island. Although genealogical links among the Papuan Timor–Alor–Pantar languages have been previously investigated, linguistic micro-studies of the hypothesized ‘shared’ ancestor languages within languages of the individual islands remain sparse. This study has three main aims: Firstly, to provide etymological reconstructions of Alor–Pantar Papuan words on a micro-level, focusing on Alor Island and specifically on plant names, which represent a cornerstone of Alor culture and history. Adopting the Comparative Method comparing cognates of 15 local languages, this research postulates historical phonetic shifts and language alignment phenomena and proposes proto-forms of the words in proto-Alor. Secondly, to shed light on possible prehistoric language contact and settlement patterns. A key finding suggests that the initial consonantal shifts *b > b > f > p in the languages is a probable loanword feature originating from the Austronesians. The geographical spread could indicate the influence of external trade and/or settlement patterns within the Papuan populations. Lastly, to provide a backbone for future etymological research on Papuan languages in Alor (and beyond) by mapping out aspects of language origins and phonetic influences and establish features of the shared proto-language(s).